MV-LV network-secure bidding optimisation of an aggregator of prosumers in real-time energy and reserve markets. (1st March 2022) - Iria, José; Scott, Paul; Attarha, Ahmad; Gordon, Dan; Franklin, Evan
Abstract: The large-scale adoption of commercial and residential distributed energy resources (DER) is transforming passive consumers into active prosumers. This new paradigm opens a door for aggregators to transform DER flexibility into electricity market services. However, it also brings new challenges for the distribution system operator (DSO) since aggregator actions may cause voltage and congestion problems in medium voltage (MV) and low voltage (LV) distribution networks. This paper addresses these challenges by proposing a new bidding optimisation strategy for an aggregator of prosumers to make network-secure bidding decisions in real-time energy and reserve markets. The bidding strategy uses the alternating direction method of multipliers on a rolling horizon framework to negotiate MV-LV network-secure bids between the aggregator and DSO, without jeopardizing the data privacy of either agent. The experiments run on a real-world case study show that the proposed bidding strategy outperforms state-of-the-art strategies, by computing MV-LV network-secure bids in fast execution times. Furthermore, the experiments also show that most of the DER value can reach the market with the proposed bidding strategy, even in heavily network-constrained scenarios of DER (up to 87% of the potential value in the most extreme DER scenario). Highlights: Network-secure participation of an aggregator in real-time electricity markets. Aggregator negotiates with the DSO to compute network-secure bids. Distributed optimisation is used to coordinate the aggregator and DSO. MV-LV network observability is required to ensure network security. Most DER value reaches the markets with our strategy even in heavily network-constrained scenarios.